PREVALENCE OF PERIODONTAL TISSUE DISEASES IN CHILDREN WITH AUTISM - D.V. Danyliuk; I.S. Dubetska-Hrabous (Український стоматологічний альманах)
It is known that among the many factors that cause dental diseases in children, disorders of mental development and disorders of the nervous system, including autism, are important. The study of dental incidence in children with autism is relevant in view of the need to develop and implement effective methods of treatment and prevention of the main dental diseases in these children.